2021
DOI: 10.1111/jan.15008
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of family resilience from the view of the adult children of parents with bipolar disorder in Chinese society

Abstract: Aims: This study explored how adult children perceived family resilience, barriers to develop family resilience and how cultural values influence their experience of parents with bipolar disorder in Chinese society. Design:A qualitative design with an interpretive phenomenological analysis of data was employed.Methods: Twenty adults who had lived with parents with bipolar disorder during childhood were recruited from the acute psychiatric ward when their parents were admitted to the hospital. They described th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Views of children about taking on parental role may indicate that the changes in family dynamics may not necessarily be problematic for them as it is a show of loyalty and wanting to be there for the parent (Liu et al, 2022;Van Parys et al, 2015). An exclusive focus on risk and resilience for children living with parental illness may conceptualise parentification as problematic.…”
Section: What Does This Paper Contribute To the Wider Global Community?mentioning
confidence: 99%
See 3 more Smart Citations
“…Views of children about taking on parental role may indicate that the changes in family dynamics may not necessarily be problematic for them as it is a show of loyalty and wanting to be there for the parent (Liu et al, 2022;Van Parys et al, 2015). An exclusive focus on risk and resilience for children living with parental illness may conceptualise parentification as problematic.…”
Section: What Does This Paper Contribute To the Wider Global Community?mentioning
confidence: 99%
“…An exclusive focus on risk and resilience for children living with parental illness may conceptualise parentification as problematic. However, listening to children themselves tell their stories about how life looks like for them could help unravel the resources they are able to enact (Liu et al, 2022) as well as how interactions with others close to them facilitate their well-being.…”
Section: What Does This Paper Contribute To the Wider Global Community?mentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, it has been reported that the experiences of chil-dren/young people coping with the difficult living conditions due to having a parent with mental illness contributed to personal development, and also that the children of parents with mental illness had strong aspects like feeling independence, empathy and resilience. 15,19,20 In another study, it was stated that children describe themselves as more mature, independent, empathetic and have gained various abilities compared to their peers (children without parents with mental illness), and they also found social support, information about mental illnesses and the support of mental health nurses to be beneficial. 21 The study findings are similar to the literature.…”
Section: Discussionmentioning
confidence: 99%